2003
DOI: 10.1097/00019605-200304000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Further delineation of Raine syndrome

Abstract: We report o a baby from an Arab family with Raine syndrome. The baby presented at birth with severe craniofacial anomalies including a wide anterior fontanelle, exophthalmos, severe depression of the nasal bridge with a hypoplastic midface, bilateral choanal atresia and a large protruding tongue. All the limbs were short and the thorax was small. Radiologically there was increased bone density in some bones, periosteal new bone formation and marked bowing of the femurs, tibiae, and ulnae. We suggest that osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 8 publications
2
25
0
Order By: Relevance
“…Raine syndrome is a lethal bone dysplasia characterized by generalized osteosclerosis with periosteal new bone formation and distinctive facies [Al-Gazali et al, 2003c]. Four consanguineous families from the UAE with several affected children were evaluated [Al-Gazali et al, 2003c] (unpublished data) and molecular study in one of those families revealed a mutation in FAM20C gene (Table 6) [Simpson et al, 2007].…”
Section: Raine Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Raine syndrome is a lethal bone dysplasia characterized by generalized osteosclerosis with periosteal new bone formation and distinctive facies [Al-Gazali et al, 2003c]. Four consanguineous families from the UAE with several affected children were evaluated [Al-Gazali et al, 2003c] (unpublished data) and molecular study in one of those families revealed a mutation in FAM20C gene (Table 6) [Simpson et al, 2007].…”
Section: Raine Syndromementioning
confidence: 99%
“…Four consanguineous families from the UAE with several affected children were evaluated [Al-Gazali et al, 2003c] (unpublished data) and molecular study in one of those families revealed a mutation in FAM20C gene (Table 6) [Simpson et al, 2007].…”
Section: Raine Syndromementioning
confidence: 99%
“…The first reported case of Raine syndrome was presented in 1989; a female neonate, born at term, who died at the age of 86 min (2). Since this original description an additional 16 cases have been described (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Radiographic studies have shown generalized increase in the density of all bones and marked increase in the ossification of the skull (13).…”
mentioning
confidence: 99%
“…[1] The osteosclerosis is usually generalized, but occasionally may be focal involving only few bones. [2] Palate usually shows cleft, but may be higharched and narrow. The babies affected with this disorder show intracranial calcifications.…”
Section: Discussionmentioning
confidence: 99%